Application of ion-exchange resin beads to produce magnetic adsorbents - Sikora Emőke; Hajdu Viktória; Muránszky Gábor; Katona Kitti Krisztina; Kocserha István; Toshiyuki Kanazawa; Fiser Béla; Bela Fiser; Фішер Бейло; Viskolcz Béla; Vanyorek László (Springer Nature, 2021)
Abstract. Heavy metal ions are among the most dangerous contaminants, which can cause serious health problems. In this work, ion-exchange resin beads were used as supports for magnetite (Fe3O4) synthesis to produce heavy metal adsorbents which can be easily separated by magnetic field. The first step of the magnetite preparation was the replacement of hydrogen ions with Fe2+ and Fe3+ ions on the sulfonic acid groups of the resin. In the second step, magnetite particle formation was induced by coprecipitating the iron ions with sodium hydroxide. The regeneration of the ion-exchange resin was also carried out by using sodium hydroxide. SEM images verified that relatively large magnetite crystal particles (diameter = 100–150 nm) were created. The ion-exchange effect of the prepared magnetic adsorbent was also confirmed by applying Cu2+, Ni2+, Pb2+ and Cd2+ ions in adsorption experiments.
Editorial board: https://link.springer.com/journal/11696/editorial-board
Contents: https://link.springer.com/journal/11696/volumes-and-issues/75-3
Keywords: heavy metal ion removal; magnetite; adsorption capacity; langmuir constant